Fitness-for-service assessment for pressurized components with crack-like flaws - Nur Nadhirah Azaar'udin (2017)
Fitness-for-service is a standard practice prepared for equipment in the oil and gas and petrochemical industry which serves as a basis for defining flaw complying to the limits and allowing engineers to identify between acceptable and unacceptable flaws and damage. The project focuses to study on assessing pressurized components with crack-like flaws mainly based on the first edition of fitness-for-service assessment, API 579 Recommended Practice (RP). The project aims to increase the efficiency on conducting fitness-for-service assessment by incorporating the procedures and calculation formulas into Microsoft Excel spreadsheet. The Excel spreadsheet consists of the key elements of fitness-for-service assessment such as the dimensions and shape of defects, the loads applied to the component, the material’s mechanical properties, and the rate of crack growth .Two example problems included by API 579 for crack-like flaw fitness-for-service assessment which were provided to demonstrate the application of the rules and evaluation procedures for Level 1 and/or Level 2 assessment were reviewed, and applied as a guideline to validate the formulas being formulated into the excel spreadsheet. The Excel spreadsheet being developed will serve as a basis of the framework for crack-like flaw fitness-for-service assessment for API 579 and future development including other types of flaws and damage.